When Marriage Guardians Refuse: Can Religious Courts Ensure Justice? - Salma, Salma Mis Aziziah; Muamar, Afif; Nursyamsudin, Nursyamsudin; Ezzerouali, Souad Ahmed; Fuad, Ibrahim Ahmed (UIR Press, 2026)
This study analyzes the judicial reasoning and legal implications of a wali adhol (unjustified refusal of a marriage guardian) decision in the Sumber Class 1A Religious Court, Case Number 83/Pdt.P/2025/PA.Sbr. The case concerns the appointment of a wali adhol to authorize the marriage contract on behalf of a prospective bride whose legal guardian refused without valid justification. The research addresses two main questions: how the concept of wali adhol is applied within the court’s decision, and how the ruling affects the legal validity of marriage and the protection of the parties’ rights. Using an empirical juridical method, this study examines court documents, judicial considerations, and procedural practices as primary data. The findings show that the court’s decision is grounded in Islamic legal principles as codified in the Compilation of Islamic Law and the Indonesian Religious Court Law. The judge determined that the refusal of the original guardian constituted adhol, thereby justifying the transfer of guardianship authority to a state-appointed guardian to ensure the validity of the marriage. The ruling confirms that the appointment of a wali adhol is legally valid and results in a lawful marriage under Indonesian Islamic family law. This article contributes to the discourse on Islamic family law in Indonesia by demonstrating how Religious Courts function as corrective institutions to prevent guardianship abuse, while ensuring both legal certainty and protection of women’s marital rights within the framework of state-administered Islamic law.